Film 99 Caya Langit di Eropa (Kajian Materi dan Metode Pendidikan Islam) - Eko Hadi Wardoyo (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
The main problem in this research is the material and methods of Islamic education contained in the 99 Light Film in the Sky of Europe. This study aims to uncover and analyze the material and methods of Islamic education. This research is a literature study (library research) using the approach of Islamic education, which on the material and methods of Islamic education with the study of deductive theory. Data collection using the method of observation and documentation methods, while to analyze the use of the method of content analysis (content analysis). The results of this study indicate that Islamic educational material in the Film 99 Light in the Sky of Europe includes aqidah material which includes: material faith in Allah SWT and faith in the books of Allah SWT, as well as halal and haram material, thaharah, tolerance and worship. While the Islamic education methods contained in the 99 99 Light in the Sky Film Europe include: discussion methods, field trips, advice methods and story methods.